Advancements in biomarker techniques for precision and safety in facial nerve identification during head and neck surgeries: a comprehensive review - Cesar Raizer; Milanie Milan; Reina Ibrahim; Joseph El Bachour; Abdelrazzak Kerhani; Gregory Nicolas (JPRAS Open)
Objective: This review aimed to evaluate biomarkers’ efficacy in enhancing facial nerve identification during head and neck surgical procedures. It summarized the literature on biomarker techniques for intraoperative visualization of the facial nerve, focusing on applications, findings, and clinical implications. Introduction: Precision is paramount in head and neck surgeries due to complex anatomical structures. In particular, facial procedures demand meticulous planning to preserve facial nerve function. Iatrogenic injuries underscore the need for advancements in nerve identification techniques. This review provided insights into biomarkers’ potential role in enhancing facial nerve identification. Methods: A PubMed search using specific keywords yielded 45 articles, with 40 meeting the initial inclusion criteria. Selection was based on relevance to facial surgery and publication in English. After screening and conflict resolution, 12 articles underwent full-text review. Results: Various biomarkers, such as fluorescent probes and retrograde tracers, have shown efficacy in improving facial nerve identification across different surgical scenarios. These techniques enhance precision in identifying nerve branches and aid in tumor resections. Conclusion: Enhanced facial nerve identification prevents nerve injuries during surgery. Although fluorescent dye-based approaches show promise, further research is needed to establish safety and long-term efficacy. Adoption of these techniques could improve patient outcomes and reduce complications.